INFLUENCE OF RESILIENCE ON QUALITY OF LIFE AMONG MILITARY PERSONNEL IN NIGERIAN DEFENCE ACADEMY KADUNA - Rukayat Oluwakemi, Kazeem; Ohunene Legbeti, Grace; Markus Shekwolo, David; Victor Fenan, Nanlir (African Journal of Social and Behavioural Sciences, 2025)
Military personnel at the Nigerian Defence Academy (NDA), Kaduna, experience high levels of stress due to rigorous training, combat preparedness, and exposure to potentially traumatic events. This study examined the impact of resilience on the quality of life (QOL) among military personnel at the Nigerian Defence Academy (NDA) in Kaduna. A cross-sectional survey design was employed, with data collected from 312 of both commissioned and non-commissioned military personnel using standardised questionnaires, including the Brief Resilience Scale (BRS) developed by Smith et al. (2008) and WHOQOL-BREF developed by WHO (1996). The research participants consisted of 236 Males (75.6%) and 76 Females (24.4%). The age range is between 18 and 60 years, with a mean age of 34.28 and a standard deviation of 9.326. The hypothesis was tested using linear and regression analyses, which revealed that resilience significantly predicted the results, indicating a significant influence on the quality of life (R² = .027, β = .341, p < .05). This explained 2.7% of the variance in quality of life. Additionally, the results indicate a significantly positive impact of resilience (β = -0.341, t = 2.952, p < .05) on Personnel quality of life. In other words, this hypothesis was confirmed significant in this study. The study concluded that resilience has a significant influence on the quality of life of military personnel at the Nigerian Defence Academy. It was recommended that the Nigerian Defence Academy should give resilience-building initiatives top priority, as they have a substantial impact on the quality of life of military personnel.